2018
DOI: 10.1038/s41598-017-18545-x
|View full text |Cite
|
Sign up to set email alerts
|

MUC4 immunohistochemistry is useful in distinguishing epithelioid mesothelioma from adenocarcinoma and squamous cell carcinoma of the lung

Abstract: The differential diagnosis of epithelioid mesothelioma from lung adenocarcinoma and squamous cell carcinoma requires the positive and negative immunohistochemical markers of mesothelioma. The IMIG guideline has suggested the use of Calretinin, D2-40, WT1, and CK5/6 as mesothelial markers, TTF-1, Napsin-A, Claudin 4, CEA as lung adenocarcinoma markers p40, p63, CK5/6, MOC-31 as squamous cell markers. However, use of other immunohistochemical markers is still necessary. We evaluated 65 epithelioid mesotheliomas,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
46
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(50 citation statements)
references
References 23 publications
4
46
0
Order By: Relevance
“…CEACAM6 and NAPSA are known to encode CEA and napsin-A, respectively, and we recently reported the efficacy of MUC4 as a negative immunohistochemical marker for the differentiation of epithelioid mesothelioma from non-small-cell lung carcinoma, either adenocarcinoma or squamous cell carcinoma. 15 Reanalysis of the microarray data from a previous study 13 was performed to generate the scatter plot, line graph and hierarchical clustering of statistically significant genes with more than a two-fold change between epithelioid mesothelioma and lung adenocarcinoma. MUC21 was identified as a novel gene of interest for further study of its utility as a basis for a negative immunohistochemical marker of epithelioid mesothelioma to differentiate it from lung adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…CEACAM6 and NAPSA are known to encode CEA and napsin-A, respectively, and we recently reported the efficacy of MUC4 as a negative immunohistochemical marker for the differentiation of epithelioid mesothelioma from non-small-cell lung carcinoma, either adenocarcinoma or squamous cell carcinoma. 15 Reanalysis of the microarray data from a previous study 13 was performed to generate the scatter plot, line graph and hierarchical clustering of statistically significant genes with more than a two-fold change between epithelioid mesothelioma and lung adenocarcinoma. MUC21 was identified as a novel gene of interest for further study of its utility as a basis for a negative immunohistochemical marker of epithelioid mesothelioma to differentiate it from lung adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Sections were incubated with the primary antibody for 2 h at room temperature, and this was followed by amplification with an Amplification Kit (Ventana). CEA, claudin‐4, TTF‐1, napsin‐A and mucin 4 (MUC4) immunohistochemistry was performed as previously described …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[13][14][15] Although Ber-EP4 and MOC-31 are reasonably sensitive as adenocarcinoma markers, both demonstrate positive staining in a subset of epithelioid mesotheliomas, which represents a potential diagnostic pitfall in effusion specimens. 14,15 A study found no membranous staining in 75 malignant mesotheliomas, although 11% (8 of 75 cases) had weak cytoplasmic staining, which is considered nonspecific. 12 In our practice, we no longer routinely use Ber-EP4 or MOC-31 because we have found claudin 4 to be more useful.…”
Section: Claudinmentioning
confidence: 99%
“…Claudin 4 shows improved sensitivity and specificity over Ber‐EP4 and MOC‐31 for distinguishing adenocarcinoma from cells of mesothelial origin . Although Ber‐EP4 and MOC‐31 are reasonably sensitive as adenocarcinoma markers, both demonstrate positive staining in a subset of epithelioid mesotheliomas, which represents a potential diagnostic pitfall in effusion specimens . A study found no membranous staining in 75 malignant mesotheliomas, although 11% (8 of 75 cases) had weak cytoplasmic staining, which is considered nonspecific .…”
Section: Introductionmentioning
confidence: 99%